2022
DOI: 10.1186/s12885-021-08992-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a ZC3H12D-regulated competing endogenous RNA network for prognosis of lung adenocarcinoma at single-cell level

Abstract: Background To identify hub genes from the competing endogenous RNA (ceRNA) network of lung adenocarcinoma (LUAD) and to explore their potential functions on prognosis of patients from a single-cell perspective. Methods We performed RNA-sequencing of LUAD to construct ceRNA regulatory network, integrating with public databases to identify the vital pathways related to patients’ prognosis and to reveal the expression level of hub genes under differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In hepatocellular carcinoma (HCC), patients with low miR-4443 expression had significantly reduced overall survival [ 12 ]. In breast cancer (BC) [ 33 ] and lung adenocarcinoma (LUAD) [ 41 ], high expression of miR-4443 resulted in decreased overall survival. Upstream regulators of miR-4443 include lncRNA FEZF1-AS1 [ 12 ] and lncRNA ENST0000630242 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hepatocellular carcinoma (HCC), patients with low miR-4443 expression had significantly reduced overall survival [ 12 ]. In breast cancer (BC) [ 33 ] and lung adenocarcinoma (LUAD) [ 41 ], high expression of miR-4443 resulted in decreased overall survival. Upstream regulators of miR-4443 include lncRNA FEZF1-AS1 [ 12 ] and lncRNA ENST0000630242 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer (BC) [ 33 ] and lung adenocarcinoma (LUAD) [ 41 ], high expression of miR-4443 resulted in decreased overall survival. Upstream regulators of miR-4443 include lncRNA FEZF1-AS1 [ 12 ] and lncRNA ENST0000630242 [ 41 ]. The overall survival rate of HCC patients with high expression of lncRNA FEZF1-AS1 was significantly decreased [ 12 ], while the overall survival rate of LUAD patients with high expression of lncRNA ENST0000630242 was increased [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo assays confirmed that lncRNA Flatr in T cells directly participated in the transcription of Foxp3 as lncRNA Flatr-deficient mice showed delayed induction of Tregs ( 72 ). Besides, high expression of ZC3H12D in Tregs and NSCLC influenced patient prognosis through the ZC3H12D-hsa-miR-4443-ENST00000630242 axis ( 73 ). The highly-expressed membrane and cytoplasmic-localized lnc-INSR aided Tregs formation of an immunosuppressive microenvironment by inducing aberrant activation of the PI3K/AKT pathway in childhood acute T lymphoblastic leukemia ( 74 ).…”
Section: The Ncrna Associated Regulatory Mechanisms Of Tregs In Cancermentioning
confidence: 99%
“…By blocking the miR-27a-3p/FOXO1 axis, ADAMTS9-AS2 can prevent the proliferation of ccRCC cells and decrease their chemoresistance (Song et al, 2019). Recent research has demonstrated that the CCCH-type zinc finger gene ZC3H12D can influence the prognosis of LUAD patients through influencing mRNA, miRNA, lncRNA, immune cells, and immunological components (Chen et al, 2022). In ccRCC, however, the predictive significance of lncRNA linked with the CCCH type of zinc fingers is unknown.…”
Section: Introductionmentioning
confidence: 99%